Barriers to innovation and firm productivity. Issue 3 (2nd April 2016) - Coad, Alex; Pellegrino, Gabriele; Savona, Maria
ABSTRACT: The paper analyzes the effect of financial, knowledge, demand, market structure and regulation barriers to innovation on firms' economic performance. It contributes to the literature on barriers to innovation by accounting for the heterogeneous effects that each barrier has on firms across the productivity distribution. We do so by employing both quantile regression techniques and matching estimators on this UK CIS panel 2002–2010 merged with the Business Structure Database. While we find evidence that both the cost and also the availability of finance negatively affect productivity across the whole distribution, the lack of qualified personnel mostly hinders high productivity firms. Moreover, quantile regression reveals some interesting variation in effect sizes across the (conditional) productivity distribution.